2016
DOI: 10.1166/jnn.2016.11992
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductivity of Diamond Packed Electrospun PAN-Based Carbon Fibers Incorporated with Multi Wall Carbon Nanotubes

Abstract: Multi wall carbon nanotubes (MWCNTs) and diamond are renowned as superlative material due to their relatively high thermal conductivity and hardness while comparing with any bulk materials. In this research, polyacrylonitrile (PAN) solution incorporated with MWCNTs at an alteration of mass fractions (0 wt%, 0.6 wt%, 1 wt%, 2 wt%) were fabricated via electrospinning under optimized parameters. Dried composite nanofibers were stabilized and carbonized, after which water base polytrafluorethylene (PTFE) mixed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Once the electrospinning process has been optimized, the effect of GNP in the thermal and electrical conductivity of PS nanofibers is studied. Figure 5 containing carbonaceous fillers and other similar systems [32][33][34]. Thermal conductivity substantially increased upon the addition of GNP, up to a 630% increase corresponding to 10 wt.% GNPs loading, in line with best results published in the scientific literature ( Figure 5(a)).…”
Section: Resultssupporting
confidence: 82%
“…Once the electrospinning process has been optimized, the effect of GNP in the thermal and electrical conductivity of PS nanofibers is studied. Figure 5 containing carbonaceous fillers and other similar systems [32][33][34]. Thermal conductivity substantially increased upon the addition of GNP, up to a 630% increase corresponding to 10 wt.% GNPs loading, in line with best results published in the scientific literature ( Figure 5(a)).…”
Section: Resultssupporting
confidence: 82%
“…In particular, the λ ⊥ and λ values of TMMFM-5 are significantly improved to 1.79 W/mK and 3.6 W/mK, about 13 and 18 times higher than that of TFM (λ ⊥ of 0.18 W/mK and λ of 0.2 W/mK), respectively. In order to reflect the excellent thermal conduction enhancement of MWCNTs, in this study, some previously reported CNT-based film-like composites are summarized in Figure 7 and Table S1 [19,28,[36][37][38][39]. Among these studies, Jang et al [39] reported that the λ value of MWCNT/PA6 increased by 232% when 10 wt% MWCNTs were introduced.…”
Section: Thermal Conductivitymentioning
confidence: 96%
“…When the content of BN amounted to 30 wt%, the λ value increased from 0.174 W/mK to 0.696 W/mK. Dong et al [28] fabricated polyacrylonitrile (PAN) by incorporating it with 2 wt% multiwalled CNTs (MWCNTs) via electrospinning, and the λ value increased by about 134% in PAN-based composites. Based on the above work, it is established that the electrospinning technique is beneficial to the directional arrangement of fillers in nanofibers, which will help to enhance in-plane heat conduction.…”
Section: Introductionmentioning
confidence: 99%